Evaluation of a Rapid Point-of-Care Fecal Antigen Detection Test for Entamoeba histolytica - Korpe, Poonum S. (The American Society of Tropical Medicine and Hygiene, 2012)
Amebiasis is a major cause of morbidity and mortality in the developing world. A reliable point-of-care test would help to improve diagnosis and early treatment. We evaluated a novel rapid fecal antigen detection test for E. histolytica (E. HISTOLYTICA QUIK CHEK; TechLab, Inc., Blacksburg, VA), in a cohort of children in Bangladesh where amebiasis is endemic. This point-of-care test had a sensitivity of 100% and a specificity of 100% when compared with enzyme-linked immunosorbent assay antigen detection.